AORN's Revised Model for Evidence Appraisal and Rating. (31st December 2015) - Spruce, Lisa; Van Wicklin, Sharon A.; Wood, Amber
Abstract: AORN perioperative practice specialists responsible for authoring the Guidelines for Perioperative Practice have spent several years using evidence‐based practice tools adapted from other organizations. AORN now has its own evidence appraisal tools and model for evidence‐based practice that can be used by nurses and students to appraise research and nonresearch articles and assign an evidence rating to help inform perioperative practice decisions. The new and revised tools include a new evidence rating model, hierarchy of evidence, and expanded appraisal tools.